(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The problematics of visuality, visualization of cultural forms, optical analysis lexicon, metaphors and images of Western culture tours become one of the important topics of postmodernist culturology. In this sense western culture starting from ancient greece and so far defined here as "Oculocentrism" (ocularcentrism).